Strategies of Entities from The SME Sector During the COVID-19 Pandemic in Poland - Lukasz BRZEZINSKI; Magdalena Krystyna WYRWICKA (Communications of International Proceedings, 2021)
Two years ago, most entrepreneurs were convinced that they recognized the environment in which they operate very well. Although the risk of unusual situations was expected, as a rule, there was a belief that the market dynamics was known. This state of feeling as if everything is known about the behavior of the environment concerned especially the entities with an established position in the sector, based on many years of experience. When the permanent global pandemic suddenly broke some long-term ties: recipient held orders, suppliers were not able to live up to the agreements, the employees feared layoffs, and government announced a lockdown and closed off borders, making it more difficult to build new business contacts. In order to stay on the market, it was necessary to undertake a wide range of activities, from the operational implementation of solutions ensuring work safety and stabilizing the financial situation of enterprises, to strategic preparations for the future. At the tactical level, many processes were accelerated, especially those related to digitization. It might even be called technological posthumanism (Gladden, 2017). The owners of entities in SME sector should especially take advantage of the use of the Internet sales and electronic communication with employees and contractors. Relations with employees who would like to be reliably informed about the company's situation are also important. The approaches to crisis management, survival strategy creation or enterprise renewal have been intensified. The aim of the research article is to analyze literature and secondary sources in terms of changes in the development and implementation of strategies in enterprises from the SME sector during a pandemic COVID-19 in Poland.
Keywords: Corporate Strategies; Small and Medium-Sized Enterprises; Pandemic Strategies; COVD-19 Pandemic; Technological Posthumanism of The Organization